Jazz Guitar Reharmonization in Malay Asli Music: A Case Study on Harmonic Adaptation in Pedagogy - Mazlan, Chamil Arkhasa Nikko; Abdullah, Mohd Hassan; Imam Koning, Sajastanah; Hidayatullah, Riyan; Jamnongsarn, Surasak; Awang Hassim, Dayang Siti Hazar (Resital: Jurnal Seni Pertunjukan, 2024)
Jazz reharmonization techniques are a well-established area of focus in Western music. However, their application to non-Western genres, such as Malay Asli music, is, at best, an unexplored area of music. This disconnect is rooted in the absence of a theoretical model, one which exists within a broader Eurocentric approach to music pedagogy that privileges Western harmony. Jazz reharmonization of Malay Asli presents challenges in cross-cultural reinterpretation and hybrid learning. This study aims to develop and evaluate a guidebook on jazz guitar reharmonization techniques to be applied in Malay Asli music. It treats the guide’s pedagogical efficacy in a cross-idiomatic context while maintaining the genre’s stylistic integrity—A qualitative case study with five jazz guitarists following a structured method book. Data consisted of assessments of performance before and after instruction, participant reflections, and semi-structured interviews. Using ISO 9241-11 measurements—efficiency, effectiveness, and satisfaction—observational analysis and participant feedback were used to measure usability. Participants exhibited improved fluency and flexibility in processing Malay Asli melodies in jazz. They recommend the guide’s poetic and flexible approach as a tool for mastering complex harmonic ideas while keeping the central idea in Malay Asli music intact. The classification of jazz harmony in stages allowed for gradual integration into their normal structural perception, which complemented their understanding of both practices. Analysis implemented through usability testing found overall acceptance of the direct scope of instructions, ordering of steps needed, and appropriate application. The study's results demonstrated how jazz reharmonization can be potent in enhancing creativity versatility within the framework of Malay Asli music and closing its traditional monopoly barriers to cross-cultural engagement through creativity. This study addresses the larger conversation of inclusive music pedagogy by connecting jazz harmony and Malay Asli aesthetics. Further engagement in hybrid music learning could involve interactive tutorials or similar digital tools explored through future research.